Observation of B s 0 - B̄ s 0 oscillations - Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2006)
We report the observation of B s0- B̄ s0 oscillations from a time-dependent measurement of the B s0-B̄ s0 oscillation frequency Δm s. Using a data sample of 1 fb -1 of pp collisions at √ = 1.96 TeV collected with the CDF II detector at the Fermilab Tevatron, we find signals of 5600 fully reconstructed hadronic B s decays, 3100 partially reconstructed hadronic B s decays, and 61500 partially reconstructed semileptonic B s decays. We measure the probability as a function of proper decay time that the B s decays with the same, or opposite, flavor as the flavor at production, and we find a signal for B s0-B̄ s0 oscillations. The probability that random fluctuations could produce a comparable signal is 8 × 10 -8, which exceeds 5σ significance. We measure Δm s = 17.77 ± 0.10(stat) ± 0.07(syst) ps -1 and extract |V td/V ts| = 0.2060 ± 0.0007(Δm s) -0.0060+0.0081 (Δm d + theor). © 2006 The American Physical Society.